Mobile Information Systems for Construction Project: Literature Review - Abbas, Nagham N.; Burhan, Abbas M. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Mobile information systems are important in many aspects, one of the most important of these aspects is the construction sector. This research provides an explanation of the theoretical aspects of mobile information systems and the nature of their relationship to construction projects. Since there are many applications and developed systems that specialize in certain aspects that were presented during the research, but at the same time this aspect needs to be further developed. It was also found that certain and multiple aspects of project management would be very feasible to develop mobile information systems for them, including cost and time management, for example.